A study of the dynamics of sunburn reduction in apple (Malus domestica) using foliar applications of boron and calcium - Mwije, Anthony (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhDAgric)--Stellenbosch University, 2020.